Social capital for sustainable tourism development in Indonesia - Gunawan Prayitno; Aidha Auliah; Ismu Rini Dwi Ari; Achmad Effendi; Ainul Hayat; Ahmad Delisa; Enock Siankwilimba; Jacqueline Hiddlestone-Mumford (Cogent Social Sciences)
Sustainable tourism development can utilize the social capital of society to encourage development. The social networks, norms, and trusts the community has built reflect social capital, which will be important for supporting and responding to sustainable tourism. The village is located in Wonosari District, Malang Regency, which is famous for its tourism village potential, namely Bangelan Village. This tourist village uses the community’s potential and natural resources, plantations, and goat farms as tourist attractions. Thus providing good benefits for the village community. This study has the H1 hypothesis: norms, social networks, and trust have a significant influence on social capital, and the H2 hypothesis: the presence of social capital has a significant influence on sustainable tourism. The sample used for this study was the Bangelan Village community, with SEM-PLS (structural equation modeling) data analysis. The study results show that the H1 and H2 hypotheses have significant and positive values. The findings show that social networks, norms, and trusts can form the social capital of the community and play an important role as a driver of sustainable tourism development in Bangelan Tourism Village.